47.5k views
5 votes
(-4x^4+5x^3-x^2+1)+(2x^4-7x^3+6x^2+2x)

Answer in standard form

User John Owen
by
5.9k points

1 Answer

5 votes

Answer by Distributing Like Terms:
-4x^4+5x^3-x^2+1+2x^4-7x^3+6x^2+2x


=-4x^4+5x^3+-x^2+1+2x^4+-7x^3+6x^2+2x

Combine Like Terms:


=-4x^4+5x^3+-x^2+1+2x^4+-7x^3+6x^2+2x\\=(-4x^4+2x^4)+(5x^3+-7x^3)+(-x^2+6x^2)+(2x)+(1)\\\=-2x^4+-2x^3+5x^2+2x+1

Answer: =−2x^4−2x^3+5x^2+2x+1

Formula rewritten in standard form:
-2x^(2) -2x^(3)+5x^(2) +2x+1

User Djra
by
5.0k points